13th IEEE International Conference on Requirements Engineering (RE'05) 2005
DOI: 10.1109/re.2005.58
|View full text |Cite
|
Sign up to set email alerts
|

Requirements engineering and the creative process in the video game industry

Abstract: The software engineering process in video game development is not clearly understood, hindering the development of reliable practices and processes for this field. An investigation of factors leading to success or failure in video game development suggests that many failures can be traced to problems with the transition from preproduction to production. Three examples, drawn from real video games, illustrate specific problems: 1) how to transform documentation from its preproduction form to a form that can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
113
2
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(128 citation statements)
references
References 20 publications
4
113
2
9
Order By: Relevance
“…The GDD is mainly a pre-production artifact which is defined by the preproduction phase team to capture a creative vision of the game. Game developers generally feel that imposing too much structure at the start of a game may be highly detrimental [40] , resulting in reduced creativity, constraining expression, and risking the intangibles that create an enjoyable feeling or experience. At the same time, the importance of structure has been highlighted by many researchers, as discussed in the literature review section (Section 2).…”
Section: Discussionmentioning
confidence: 99%
“…The GDD is mainly a pre-production artifact which is defined by the preproduction phase team to capture a creative vision of the game. Game developers generally feel that imposing too much structure at the start of a game may be highly detrimental [40] , resulting in reduced creativity, constraining expression, and risking the intangibles that create an enjoyable feeling or experience. At the same time, the importance of structure has been highlighted by many researchers, as discussed in the literature review section (Section 2).…”
Section: Discussionmentioning
confidence: 99%
“…The result of this literature review showed that the main emphasis in this research domain is on requirement engineering, as well as coding tools and techniques. Articles related to requirement engineering focuses on the problem of going from a game concept that should be fun and engaging to functional requirements, and software architectures and software designs that can produce game software realizing the game concept [7]. The initial requirements for a game can be labeled emotional requirements that contain the game designer's intent and the means which the game designer expects the production team to induce that emotional state in the player [4].…”
Section: Related Workmentioning
confidence: 99%
“…Another example is that game development does not include functional requirements from the end-users. Typical end-user requirements to a game is that the game must be fun and engaging [7]. The latter poses a challenge of going from preproduction phase that produces a game design document (and maybe a prototype), to the production phase where all the software, game design, art, audio and music will be produced [7].…”
Section: Changes Over Timementioning
confidence: 99%
See 1 more Smart Citation
“…In general, the direct interaction with the users, if present, is confined in the final phase of testing and validation. In [12], the video games production process is analyzed, by taking into account the emotional factors that can influence it. Similarly, Hunicke et al ( [13]) study the production process of games, trying to bridge the gap between design and development, game criticism, and technical game research.…”
Section: Related Workmentioning
confidence: 99%